Pembelaan Jalal Al-Din Al-Suyuti Atas Kritik Ibn Jauzi Terhadap Hadis Sunan Abi Daud - huda, ikmal tahjibil; Muhid; Baitul Hantira (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This research explores Ibn Jauzi's criticism of the hadiths in Abu Dawood's Sunan, followed by al-Suyuti's defense. The hadiths deemed maud'u (fabricated) by Ibn Jauzi are documented in his work titled